Psychosocial workload and stress in the workers' representative - Rabe Martin; Giacomuzzi Salvatore; Nübling Matthias (BMC, 2012)
Abstract Background Using a data set of works councils of trade union IG Metal, this paper investigates psychosocial stress and strain on this specific group in comparison to employees working in administration in general (leadership and non-leadership-role) and a national reference value. Methods For assessing psychosocial work factors on works councils within the sector represented by the trade union IG Metal in Germany, a research by using the German standard version of COPSOQ (Copenhagen Psychosocial Questionnaire) was performed. The instrument includes 87 single items forming 25 aspects of strain and stress. Results from the study group of works councils were compared to those from employees working in administration and to the general population mean (COPSOQ database). Statistical analysis included t-tests, analysis of variance and multiple comparisons of means. To be significant in terms of statistics, p<0.05 (two-tailed) and a minimum deviation of 5 or more points between groups' mean values identify the relevant values. Results All in all, 309 works councils from a national survey of the German chemical and metalworking industries took part in the study. 113 were full-time works council members (exempted from the duty to perform their regular work), 196 were voluntary members (acting as employee representatives on an honorary basis alongside their normal duties). Comparison between works councils and employees working in administration (leadership roles (N=1810) and non-leadership roles (N=2970)) and for employees in general (N=35.000) showed unfavourable values for works councils for most scales. Significantly higher values indicating higher strain and stress were found for the scales: emotional demands, work-privacy conflict, role conflicts, mobbing, cognitive stress symptoms and burnout. Unfavourable results were obtained for the aspects: quality of leadership, social support, sense of community and general health. Favourable findings were found on the scales: influence at work, quantity of social relations and the partly positive values for quantitative demands and commitment to the workplace. Conclusion Compared to the reference groups, works council members perceive the psychosocial demands of working life as more exhausting for the majority of aspects. This allows several conclusions. One reason may be the extended tasks employee representatives face, an other may be that the education of most works council members does not seem appropriate to the high demands of their managerial and executive tasks.